2022
DOI: 10.1007/s00277-022-04959-9
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity characteristics of multiple myeloma patients diagnosed in Finland 2005–2016

Abstract: Multiple myeloma (MM) patients are predominantly elderly with comorbidities that have an impact on patient mortality and treatment decisions. We previously reported the patient characteristics and overall survival outcomes of the Finnish MM cohort diagnosed between 2005 and 2016 in a nationwide retrospective registry study comprising 3,851 adults. Here, we report detailed comorbidity characteristics for this real-world Finnish MM population at cohort entry and during follow-up. Data on diagnoses and causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(63 reference statements)
1
4
0
1
Order By: Relevance
“…Deeper responses were achieved in earlier lines of therapy, further emphasizing the importance of optimizing treatment sequencing [27,39]. It is noteworthy that a recent Finnish cohort study reported that the comorbidity burden in the Finnish MM population is high, especially the prevalence of cardiovascular diseases and secondary malignancies, in line with previous observations [40][41][42][43]. This further highlights the fact that there are profound differences between the real-world patient populations and those run under strictly controlled clinical trial protocols.…”
Section: Discussionsupporting
confidence: 68%
“…Deeper responses were achieved in earlier lines of therapy, further emphasizing the importance of optimizing treatment sequencing [27,39]. It is noteworthy that a recent Finnish cohort study reported that the comorbidity burden in the Finnish MM population is high, especially the prevalence of cardiovascular diseases and secondary malignancies, in line with previous observations [40][41][42][43]. This further highlights the fact that there are profound differences between the real-world patient populations and those run under strictly controlled clinical trial protocols.…”
Section: Discussionsupporting
confidence: 68%
“…Cardiovascular comorbidities are common in patients with MM and occur due to patient-, disease-, or treatment-related factors (20). As most MM drugs can have adverse effects, especially on the cardiovascular system, these comorbidities can pose a challenge when assessing the optimal treatment course and outcomes in patients with MM (21). Therefore, it is crucial to record and manage comorbidities alongside MM treatment for the optimal management of MM.…”
Section: Discussionmentioning
confidence: 99%
“…When patients with RRMM receive anti-myeloma therapy after failure of early lines of therapy, they may present with a worse clinical status and comorbidities than at the time of diagnosis (Song et al 2016;Toppila et al 2022), which may be due to the disease progression itself or the cumulative effect of therapy-related toxicity. Previous reports have showed that these debilitating features are associated with poor outcomes in RRMM patients.…”
Section: Discussionmentioning
confidence: 99%